The Potential uses of underutilized plant species for the mass production of Trichoderma harzianum L. - Perera, R S M T I; Jayawardana, H H; Mubarak, A N M; Nashath, M N F; Shafna, A M (SAARC Journal of Agriculture, 2023)
Several plant diseases can be controlled biologically using Trichoderma spp. However, the mass production and storage of Trichoderma spp. is highly expensive. Therefore, this research was carried out at Fruit Crop and Development Center, Horana, Sri Lanka to screen the effects of leaves of four different crops and another 13 underutilized wild plant species on their suitability in the mass production of Trichoderma harzianum L. Seventeen different media were prepared using green leaves (5g) of individual plant species comprised with glucose (5g/L) and distilled water (50ml). Treatments were arranged in Complete Randomized Design (CRD) with five replications. Spore counts of fungus were recorded using hemocytometer at 1st, 2nd, 3rd and 4th week after inoculation. Different treatments showed significant variations in spore counting of T. harzianum after 1st, 2nd, 3rd and 4th week of inoculation (p<0.05). Castor (9.8x107 CFU/ml), gadapana (9.64x107 CFU/ml) and erabadu (9.64x107 CFU/ml) had significantly higher spore count at the 1st week while kappettiya (25.31x107 CFU/ml) and habarala (25.21x107 CFU/ml) had the highest values at 2nd week. Significantly increased spore count of 61.5x107 CFU/ml and 61.2x107 CFU/ml were resulted from castor and kappettiya during 3rd week after inoculation. However, a sharp increase in spore count was found at 4th week, particularly in wal sooriya kantha (157.17x107 CFU/ml) while in contrary, the lemon, rambutan, bovitiya, jack and mango leaves showed poor performances in the mass production of T. harzianum. Based on these results, wal sooriya kantha can be successfully used as growing media for T. harzianum. SAARC J. Agric., 21(1): 79-87 (2023)